2014
DOI: 10.12968/ijpn.2014.20.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Quality of end-of-life care for those who die at home: views and experiences of bereaved relatives and carers

Abstract: Little is known about the quality of the end-of-life care patients receive at home. This paper reports findings from a study that explored bereaved relatives' and carers' experiences of end-of-life care at home using the Care of the Dying Evaluation (CODE) questionnaire. Narrative data from questionnaires completed by 72 carers of patients who had died at home in the North West of England underwent qualitative analysis. In general good quality care was provided, but there were times when adequate support was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The potentially different or conflicting needs of dying people and their family carers are described in the literature,7 32 but our study develops this theme, adding important details to aid crucial understanding of how the home as a setting contributes to conflicting emotions. The satisfaction of the perception of having supported a ‘good death’ appeared to be key in enabling many of the family carers to tolerate significant changes to their own routines and environment while striving to maintain normality for the dying person.…”
Section: Discussionmentioning
confidence: 96%
“…The potentially different or conflicting needs of dying people and their family carers are described in the literature,7 32 but our study develops this theme, adding important details to aid crucial understanding of how the home as a setting contributes to conflicting emotions. The satisfaction of the perception of having supported a ‘good death’ appeared to be key in enabling many of the family carers to tolerate significant changes to their own routines and environment while striving to maintain normality for the dying person.…”
Section: Discussionmentioning
confidence: 96%
“…To improve the care, we need to be able to assess the current quality of care in a reliable manner. One internationally recognized method for evaluating care for dying patients is to ask bereaved relatives through post-bereavement surveys [ 8 , 9 ]. ‘Care Of the Dying Evaluation’ (CODE™) is a recognised, validated post-bereavement questionnaire focused on both quality of patient care and support for the relatives in the patient’s last 2 days of life and the immediate post-bereavement period [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…One internationally recognized method for evaluating care for dying patients is to ask bereaved relatives through post-bereavement surveys [ 8 , 9 ]. ‘Care Of the Dying Evaluation’ (CODE™) is a recognised, validated post-bereavement questionnaire focused on both quality of patient care and support for the relatives in the patient’s last 2 days of life and the immediate post-bereavement period [ 8 ]. In addition to questions with pre-determined response categories asking about nursing and medical care, symptom relief, communication, emotional and spiritual support, and circumstances surrounding the death, responders may add free text comments.…”
Section: Introductionmentioning
confidence: 99%
“…This result was mirrored both by the work of Eilegard et al (2013) who found that 99% of their participants stated that the study was valuable and they welcomed the chance to tell their bereavement story, and also by Stiel et al (2015) who found that their participants had a high willingness to participate and stated they benefited from the research discussions, reporting low to moderate levels of burden (Stiel et al, 2015). Lees et al (2014) also reported that a specific finding from their work was that participants positively welcomed the opportunity to talk about their experiences of being alongside a loved one at the end of life.…”
Section: Resultsmentioning
confidence: 90%